The Effect of the Resin Type and Filling Placement Techniques on the Degree of Conversion of Various Resin-Based Composites - Ayse Nurcan Duman; Pinar Cevik; Arife Doğan (Applied Sciences)
The degree of conversion (DC) is crucial in determining the mechanical and clinical performance of resin-based composites (RBCs). This in vitro study aimed to evaluate the effect of the resin type and placement technique on the DC of RBCs (micro-hybrid, packable, hybrid, ormocer-based and flowable) polymerized with a second-generation LED light-curing unit (LCU). A total of 75 RBC samples were divided into three groups. Each RBC was placed into 4 mm diameter and 2 and 8 mm heigh Teflon molds with conventional standard, bulk, and incremental techniques (n = 5) and polymerized by LED LCU (229.153 mW/cm2) using the standard mode. After 24 h, DC was determined by FTIR spectrophotometry. The data were analyzed with two-way ANOVA and Tukey’s HSD test (p < 0.05). The DC of the RBCs varied between 62.8 and 29.2%. While the same DC was obtained for 2 mm samples at the top and the bottom surfaces, the DC of the 8 mm samples gradually diminished from the top surface to the bottom surface. Significant differences were observed in the DC of the RBCs. An optimal DC was obtained for packable, micro-hybrid and ormocer-based RBCs polymerized by LED LCU with the recommended curing times. Considering that the polymerization process is versatile, further in vitro studies are needed.